Cell Metabolism and DNA Repair Pathways: Implications for Cancer Therapy - Sobanski, Thais; Rose, Maddison; Suraweera, Amila; O’Byrne, Kenneth; Richard, Derek J.; Bolderson, Emma (Frontiers in Cell and Developmental Biology, 2021)
DNA repair and metabolic pathways are vital to maintain cellular homeostasis in normal human cells. Both of these pathways, however, undergo extensive changes during tumourigenesis, including modifications that promote rapid growth, genetic heterogeneity and survival. While these two areas of research have remained relatively distinct, there is growing evidence that the pathways are interdependent and intrinsically linked. Therapeutic interventions that target metabolism or DNA repair systems have entered clinical practice in recent years, highlighting the potential of targeting these pathways in cancer. Further exploration the links between metabolic and DNA repair pathways may open new therapeutic avenues in the future. Here, we discuss the dependence of DNA repair processes upon cellular metabolism; including the production of nucleotides required for repair, the necessity of metabolic pathways for the chromatin remodelling required for DNA repair, and the ways in which metabolism itself can induce and prevent DNA damage. We will also discuss the roles of metabolic proteins in DNA repair and, conversely, how DNA repair proteins can impact upon cell metabolism. Finally we will discuss how further research may open therapeutic avenues in the treatment of cancer.